Impact of ladder‐related falls on the emergency department and recommendations for ladder safety. (14th September 2017) - Cabilan, CJ; Vallmuur, Kirsten; Eley, Rob; Judge, Chantelle; Cochrane, Sarah; Reed, Connie; Riordan, Jessica; Roberts, Kym; Thom, Ogilvie; Wood, Gabriella
Abstract: Objectives: To describe the characteristics of patients who presented to the ED from a ladder‐related fall and their injuries, highlight the impact of ladder‐related falls on the ED, identify contributing factors of ladder falls and draw recommendations to improve ladder safety. Methods: A prospective observational study was conducted in two EDs. Patients' demographics and ED services used were obtained from medical records. A 53‐item questionnaire was used to gather information about the type of ladder used, ladder activity, circumstances of the fall, contributing factors and future recommendations. Results: A total of 177 patients were recruited for this study. The typical patient was male, over the age of 50 and using a domestic ladder. The ED length of stay was between 30 min and 16 h, and was longer if patients were transferred to the short stay unit. Services most utilised in the ED included diagnostic tests, procedures and referrals to other healthcare teams. Most falls occurred because of ladder movement and slips or misstep. The major contributing factors identified were a combination of user features and flaws in ladder setup. Conclusions: Ladder‐related falls carry a considerable burden to the ED. Recommendations include ladder safety interventions that target ladder users most at risk of falls: men, ≥50 years old and performing domestic tasks. Safety interventions should emphasise task avoidance, education and training, utilisation of safety equipment and appropriate ladder setup.